2016
DOI: 10.2217/cer-2016-0024
|View full text |Cite
|
Sign up to set email alerts
|

Physicians’ perspectives regarding pragmatic clinical trials

Abstract: Aim: Practicing physicians inevitably become involved in pragmatic clinical trials (PCTs), including comparative effectiveness research. We sought to identify physicians’ perspectives related to PCTs. Methods: In-depth semistructured interviews with 20 physicians in the USA. Results: Although physicians are generally willing to participate in PCTs, their support is predicated on several factors including expected benefits, minimization of time and workflow burdens and physician engagement. Physicians communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Data are collected during the course of routine care, and partnerships must be built with healthcare providers to ensure that the intervention can be added into existing workflows as seamlessly and with as little burden as possible [ 42 ]. Physicians, nurses, and other clinical staff who will implement the protocol will have insight about the feasibility and sustainability of the intervention [ 43 ]. For example, the PPACT trial has an intervention that is delivered in the primary care setting where schedules are busy and space is tight.…”
Section: Results: Lessons Learnedmentioning
confidence: 99%
“…Data are collected during the course of routine care, and partnerships must be built with healthcare providers to ensure that the intervention can be added into existing workflows as seamlessly and with as little burden as possible [ 42 ]. Physicians, nurses, and other clinical staff who will implement the protocol will have insight about the feasibility and sustainability of the intervention [ 43 ]. For example, the PPACT trial has an intervention that is delivered in the primary care setting where schedules are busy and space is tight.…”
Section: Results: Lessons Learnedmentioning
confidence: 99%
“…Engaging clinicians in research when they are not directly involved as investigators is a challenge that should be anticipated by researchers planning future pragmatic trials. [37][38][39] Our analysis of the variance within session duration categories suggests that for intervention facilities, the extent of intervention uptake was driven in large part by facility-level rather than patient-level factors. More work is needed to identify the relevant facility factors, which might include facility size, number of nephrologists, leadership approaches, staffing ratios and stability, and competing initiatives.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, questions of consent in pragmatic trials have been consistently raised as topics of interest and have been studied through vignette-based research with healthcare professionals and patients [ 36 , 37 ], interviews with physicians [ 39 ], deliberative engagement activities [ 42 ] and surveys [ 41 ]. For example, in a study using case vignettes, respondents preferred specific disclosure and options to either opt-in or opt-out of research compared to a general policy in which patients were informed broadly that a healthcare system engages in Comparative Effectiveness Research (CER) [ 37 , 42 ] .…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have explored attitudes toward consent under different trial scenarios. This work found that attitudes toward consent differed not only by the type of intervention, but also due to different design elements such as randomization and the degree to which the trial design departed from routine clinical care [ 39 ].…”
Section: Introductionmentioning
confidence: 99%